Scalp cooling to prevent chemotherapy-induced alopecia, - Giselle de Barros Silva; Kathryn Ciccolini; Aline Donati; Corina van den Hurk (Sociedade Brasileira de Dermatologia, 2020)
Abstract Chemotherapy-induced alopecia causes an important impact on cancer patients and its risk of persistence is currently a considerable issue in cancer survivors. Of the various interventions proposed for the prevention of chemotherapy-induced alopecia, scalp cooling has emerged as an effective and safe strategy. This paper aims to provide an overview on scalp cooling and chemotherapy-induced alopecia prevention.